Nutraceutical Properties of Optimized Composite Natural Additive Powder Containing Ginger, Hibiscus Calyx, and Sweet Detar Seed - Abigael Odunayo Bankole; Emmanuel Anyachukwu Irondi; Wasiu Awoyale; Precious Omolara Akinlabu; Emmanuel Oladipo Ajani; Emmanuel Oladeji Alamu (Food ScienTech Journal, 2026)
Natural food additives are gaining more research attention due to their acclaimed safety and nutritive and nutraceutical benefits. Consumers could derive more nutraceutical benefits if different natural food additives are blended. This study investigated the nutraceutical properties (bioactive composition, antioxidant, and enzyme-inhibitory activity) of an optimised composite natural additive powder formulated with ginger rhizome, hibiscus calyx, and sweet detar seed. An optimised blend of ginger, hibiscus, and sweet detar, serving as natural flavourant, colourant, and thickener, respectively, was formulated using the Design Expert Software. Their synthetic counterpart, comprising vanilla flavour, red colourant, and sodium carboxymethylcellulose, was prepared in the same ratio as control. The native additives and their composites were analysed for total phenolics, flavonoids, tannins, and saponins, alongside antioxidant activity (Fe3+-reducing power, ABTS*+- and DPPH*-scavenging assays). Inhibitory activities of the additives against α-glucosidase, α-amylase, pancreatic lipase, and angiotensin I-converting enzyme (ACE) were also determined using standard methods. The composite natural additive possessed higher (p